Protocol for a multinational risk-stratified randomised controlled trial in paediatric Crohn's disease: methotrexate versus azathioprine or adalimumab for maintaining remission in patients at low or high risk for aggressive disease course. Issue 7 (1st July 2020) - Harris, Rachel E; Aloi, Marina; de Ridder, Lissy; Croft, Nicholas M; Koletzko, Sibylle; Levine, Arie; Turner, Dan; Veereman, Gigi; Neyt, Mattias; Bigot, Laetitia; Ruemmele, Frank M; Russell, Richard K
Abstract : Introduction: Immunomodulators such as thiopurines (azathioprine (AZA)/6-mercaptopurine (6MP)), methotrexate (MTX) and biologics such as adalimumab (ADA) are well established for maintenance of remission within paediatric Crohn's disease (CD). It remains unclear, however, which maintenance medication should be used first line in specific patient groups. Aims: To compare the efficacy of maintenance therapies in newly diagnosed CD based on stratification into high and low-risk groups for severe CD evolution; MTX versus AZA/6MP in low-risk and MTX versus ADA in high-risk patients. Primary end point: sustained remission at 12 months (weighted paediatric CD activity index ≤12.5 and C reactive protein ≤1.5 fold upper limit) without relapse or ongoing requirement for exclusive enteral nutrition (EEN)/steroids 12 weeks after treatment initiation. Methods and analysis: REDUCE-RISK in CD is an international multicentre open-label prospective randomised controlled trial funded by EU within the Horizon2020 framework (grant number 668023). Eligible patients (aged 6–17 years, new-onset disease receiving steroids or EEN for induction of remission for luminal ± perianal CD are stratified into low and high-risk groups based on phenotype and response to induction therapy. Participants are randomised to one of two treatment arms within their risk group: low-risk patients to weekly subcutaneous MTX or daily oral AZA/6MP, and high-risk patients to weekly subcutaneous MTX or fortnightly ADA. Patients are followed up for 12 months at prespecified intervals. Electronic case report forms are completed prospectively. The study aims to recruit 312 participants (176 low risk; 136 high risk). Ethics and dissemination: ClinicalTrials.gov Identifier: (NCT02852694 ), authorisation and approval from local ethics committees have been obtained prior to recruitment. Individual informed consent will be obtained prior to participation in the study. Results will be published in a peer-reviewed journal with open access. Trial registration number: NCT02852694 ; Pre-results.